Customer Satisfaction In An Ems Company - K. Suppiah, Thiruchelvam (2015)
Increasing competition in an increasingly globalized world drives the need of companies’ to retain their customers. Ensuring Customer Satisfaction is a key strategic imperative for any company in this battle to retain customers